WAJIB PAJAK PADA E-FILING DI KANTOR PELAYANAN PAJAK PRATAMA KOTA KEDIRI - Solikah, Mar’atus; Kusumaningtyas, Dian (Universitas Nusantara PGRI Kediri, 2017)
E-filing is a service of charging and delivering Letter of Notification (SPT) electronically to Directorate General of Taxes, by utilizing internet communication channel. The purpose of this research is to know how the implementation of e-filing based on its dimension and know the characteristics of reporting compliance. The population in this study are all personal tax payers in Kediri, the sampling technique sampling sampling with a total of 200 samples. Data collection using questionnaire. Dimensions in e-filing variables in this study are System Quality, Quality of Information, Usage, User Satisfaction. Data analysis technique using SPSS. The results of the research Overall taxpayers are satisfied with the existence of e-filing system while for the characteristics of compliance reporting Annual Notice by using e-filing system able to help taxpayers avoid the delay of SPT reporting, avoid the arrears and fines of delay in reporting the Annual SPT. Keywords: e-filing, taxes